Knowledge on Hazardous Effects of Alcohol among Caregivers of Mentally Ill - George , Ansiem (International Journal of Psychosocial Rehabilitation, 2020)
The detrimental effects of alcohol results in 2.5 million deaths annually, as per the global information system on alcohol and health. The study aimed to assess the awareness regarding hazardous effects of alcoholism among caregivers of mentally ill clients, mental health centre, Trivandrum. The objectives were -To find out the level of knowledge on the hazardous effects of alcohol among caregivers of mentally ill,To find out the association between level of knowledge and selected socio demographic variables (age of individual, place of residence, marital status, educational status of father, educational status of mother, economic status of family, family history of alcoholism). The study found that 28.33% had poor knowledge, 63.34% (38) had average knowledge, and 8.33% (5) of the caregivers had good knowledge .The study also revealed significant association between selected socio demographic variables like age, educational status of mother, educational status of father, place of residence and family history of alcoholism.